2013
DOI: 10.1002/eji.201142340
|View full text |Cite
|
Sign up to set email alerts
|

The NF‐κB binding site located in the proximal region of the TSLP promoter is critical for TSLP modulation in human intestinal epithelial cells

Abstract: Thymic stromal lymphopoietin (TSLP) is constitutively secreted by intestinal epithelial cells. It regulates gut DCs, therefore, contributing to the maintenance of immune tolerance. In the present report, we describe the regulation of TSLP expression in intestinal epithelial cells and characterize the role of several NF-κB binding sites present on the TSLP promoter. TSLP expression can be stimulated by different compounds through activation of p38, protein kinase A, and finally the NF-κB pathway. We describe a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 42 publications
5
46
0
Order By: Relevance
“…We found that dexamethasone and Bay 11-7082 inhibited TSLP and IL33 expression by downregulating IRF3 and NF-κB activities. Coincidentally, the essential roles of the IRF3 and NF-κB pathways in TSLP and IL-33 induction were demonstrated in other research models [(16, 7175), Schuijs et al (76) #5788]. Moreover, we found that LPS-modulated IRF3 and NF-κB activation in the polyI:C or HPeV1/TLR3 axis could be the causal mechanism of hygiene hypothesis.…”
Section: Discussionsupporting
confidence: 76%
“…We found that dexamethasone and Bay 11-7082 inhibited TSLP and IL33 expression by downregulating IRF3 and NF-κB activities. Coincidentally, the essential roles of the IRF3 and NF-κB pathways in TSLP and IL-33 induction were demonstrated in other research models [(16, 7175), Schuijs et al (76) #5788]. Moreover, we found that LPS-modulated IRF3 and NF-κB activation in the polyI:C or HPeV1/TLR3 axis could be the causal mechanism of hygiene hypothesis.…”
Section: Discussionsupporting
confidence: 76%
“…It has been shown, however, that the TSLP promoter contains several binding sites for the p65 subunit of NF-κB; a transcription factor shown to be TRAIL dependent in AAD [41] which we show is also repressed in the oesophagus of TRAIL−/− in the EoE model. It has also been shown that the subsequent expression of TSLP in intestinal epithelia cells is dependent on NF-κB [41]. Given NF-κB is upregulated in EoE patients [42], it is possible that TRAIL is a key regulator of TSLP through p65 activation and contributes to EoE most likely through basophil activation [25].…”
Section: Discussionmentioning
confidence: 50%
“…It is still unknown how TSLP is regulated by TRAIL in EoE, given that no link between TRAIL and TSLP was evident in models of AAD [29]. It has been shown, however, that the TSLP promoter contains several binding sites for the p65 subunit of NF-κB; a transcription factor shown to be TRAIL dependent in AAD [41] which we show is also repressed in the oesophagus of TRAIL−/− in the EoE model. It has also been shown that the subsequent expression of TSLP in intestinal epithelia cells is dependent on NF-κB [41].…”
Section: Discussionmentioning
confidence: 65%
“…Several promising screenings were already implemented such as models of gut epithelial layer integrity, inflammation, immune cell maturation and immune-modulation, cell differentiation and proliferation, metabolism regulations and hormone secretion. These gave rise to the identification of original mechanisms of action and a range of publications and patents [76,[78][79][80][81][82][83][84][85][86][87][88].…”
Section: Microbiota As Source Of Novel Drugs Adjuvants and Targetsmentioning
confidence: 99%